Newly identified wild rice accessions conferring high salt tolerance might use a tissue tolerance mechanism in leaf - Prusty, Manas R.; Kim, Sung-Ryul; Vinarao, Ricky; Entila, Frederickson; Egdane, James; Diaz, Maria G. Q.; Jena, Kshirod K. (Frontiers Media, 2018)
Cultivated rice (Oryza sativa L.) is very sensitive to salt stress. So far a few rice landraces have been identified as a source of salt tolerance and utilized in rice improvement. These tolerant lines primarily use Na+ exclusion mechanism in root which removes Na+ from the xylem stream by membrane Na+ and K+ transporters, and resulted in low Na+ accumulation in shoot. Identification of a new donor source conferring high salt tolerance is imperative. Wild relatives of rice having wide genetic diversity are regarded as a potential source for crop improvement. However, they have been less exploited against salt stress. Here, we simultaneously evaluated all 22 wild Oryza species along with the cultivated tolerant lines including Pokkali, Nona Bokra and FL478, and sensitive check varieties under high salinity (240 mM NaCl). Based on the visual salt injury (VSI) score, three species (O. alta, O. latifolia and O. coarctata) and four species (O. rizhomatis, O. eichengeri, O. minuta and O. grandiglumis) showed higher and similar level of tolerance compared to the tolerant checks, respectively. All three CCDD genome species exhibited salt tolerance, suggesting that the CCDD genome might possess the common genetic factors for salt tolerance. Physiological and biochemical experiments were conducted using the newly isolated tolerant species together with checks under 180 mM NaCl. Interestingly, all wild species showed high Na+ concentration in shoot and low concentration in root unlike the tolerant checks. In addition, the wild tolerant accessions showed a tendency of a high tissue tolerance in leaf, low malondialdehyde level in shoot, and high retention of chlorophyll in the young leaves. These results suggest that the wild species employ tissue tolerance mechanism to manage salt stress. Gene expression analyses of the key salt tolerance-related genes suggested that high Na+ in leaf of wild species might be affected by OsHKT1;4-mediated Na+ exclusion in leaf and the following Na+ sequestration in leaf might be occurring independent of tonoplast-localized OsNHX1. The newly isolated wild rice accessions will be valuable materials for both rice improvement to salinity stress and the study of salt tolerance mechanism in plants